2016
DOI: 10.1002/mdc3.12422
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Anti‐Parkinson Drug Use in a Nationally Representative Sample

Abstract: Background Although numerous prescription drugs are available to treat Parkinson's disease (PD), little is known about national use in clinical practice and which factors may influence variability in care. The objectives of this study were to describe the prevalence of anti‐Parkinson drug use among Medicare beneficiaries with PD and to identify demographic and clinical factors associated with drug use. Methods This retrospective study was based on a random sample of annual 5% Medicare Part A and B claims linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 36 publications
3
44
1
1
Order By: Relevance
“…Dahodwala et al, showed that African-Americans are four times less likely than White PD patients to receive PD treatment (OR 0.24; 95% CI 0.09-0.64) [158]. This finding has been replicated [157,159] and there is evidence the inequalities extend to the treatment of depression and advanced therapies in PD patients as well [160][161][162]. Amongst the minority ethnic patients that do receive treatment prescribing errors are more likely; Hispanic PD patients have an increased probability of being co-prescribed an anticholinesterase inhibitor and a high potency anticholinergic; a frank prescribing error [122].…”
Section: Healthcare Inequalitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Dahodwala et al, showed that African-Americans are four times less likely than White PD patients to receive PD treatment (OR 0.24; 95% CI 0.09-0.64) [158]. This finding has been replicated [157,159] and there is evidence the inequalities extend to the treatment of depression and advanced therapies in PD patients as well [160][161][162]. Amongst the minority ethnic patients that do receive treatment prescribing errors are more likely; Hispanic PD patients have an increased probability of being co-prescribed an anticholinesterase inhibitor and a high potency anticholinergic; a frank prescribing error [122].…”
Section: Healthcare Inequalitiesmentioning
confidence: 93%
“…This may in-part explain some of the suspected under-ascertainment of PD in patients from certain ethnic backgrounds. For PD patients, being treated by a neurologist was inversely associated with residing in a nursing home, hip fractures and likelihood of death [155,157]. Dahodwala et al, showed that African-Americans are four times less likely than White PD patients to receive PD treatment (OR 0.24; 95% CI 0.09-0.64) [158].…”
Section: Healthcare Inequalitiesmentioning
confidence: 99%
“…Imipramine [247] Isobavachalcone [248] Isochlorogenic acid [167] Isoquercetin (Isoquercitrin) [249] Kaempferol [128,160,193,194] Kaempferol, 3-O-a-l arabinofuranoside-7-O-a-l-rhamnopyranoside [214] KR33493 [250] Kukoamine [251] Lestaurtinib [164] Lipoic acid [252][253][254] Luteolin [128] LY354740 [115] M10 [24] M30 (VAR10303) [112,255] M99 [24] Macranthoin G [256] Magnesium lithospermate B [257] [160,193,194,267] [18F]MPPF [107] MSX-3 [268] Myricetin [128,269,270] Myricitrin [271] Naringenin [128,272] Naringin [117,273,274] Nicotinamide adenine dinucleotide phosphate (NADPH) [275,276] Nicotinamide mononucleotide [277] Nitecapone [278] Nordihydroguaiaretic [160,193,194] Oleuropein…”
Section: Compound Name(s) Referencesmentioning
confidence: 99%
“…Previous database studies from the United States [8][9][10][11], Taiwan [12], and Japan [13] have examined prescribing patterns for PD. However, the Japanese study reported data obtained before publication of the 2011 guidelines, and new anti-PD drugs have been approved and new data regarding the risk of side effects have been reported since then [14].…”
Section: Introductionmentioning
confidence: 99%